Sedentary Patterns and Systemic Inflammation: Sex-Specific Links in Older Adults - Bergens, Oscar; Nilsson, Andreas; Papaioannou, Konstantinos-Georgios; Kadi, Fawzi (Frontiers in Physiology, 2021)
The study aimed to examine sex-specific associations between objectively measured sedentary patterns and pro- and anti-inflammatory biomarkers in older adults when considering the moderating impact of physical activity (PA). Accelerometer-based monitoring of sedentary patterns and PA was conducted in a population of older men (n = 83; age: 67.4 ± 1.5; height: 178.7 ± 6.6 cm; weight: 80.9 ± 10.6 kg) and women (n = 146; age: 67.4 ± 1.6; height: 164.2 ± 6.1 cm; weight: 64.6 ± 10.1 kg) aged 65–70. Blood samples were collected for the assessment of the inflammatory biomarkers C-reactive protein (CRP), fibrinogen, interleukin-6 (IL-6), IL-10, IL-18, and monocyte chemoattractant protein-1 (MCP-1). Data were analyzed using multiple linear regression models. Total and bouts of ≥10 min of sedentary time were inversely associated with the anti-inflammatory marker IL-10 in older men (accumulated sedentary time: β = −0.116; bouts: β = −0.099; all p < 0.05). Associations were independent of moderate-to-vigorous physical activity (MVPA) and total PA volume. In women, total and bouts of ≥10 min of sedentary time were detrimentally associated with the pro-inflammatory marker fibrinogen (accumulated sedentary time: β = −0.130; bouts: β = −0.085; all p < 0.05). Associations remained between accumulated sedentary time and fibrinogen when adjusting for MVPA and total PA volume. This study highlights sex-specific routes by which sedentary patterns impact on pro- and anti-inflammatory biomarkers in older adults. The findings support efforts to promote accumulation of time spent in PA at the expense of time in sedentary pursuits on low-grade inflammation in older men and women.